Unions and the Labor Market for Managers - Jörn-Steffen Pischke; Kevin F. Hallock; John DiNardo (Institute for the Study of Labor (IZA), 2000)
We examine the relationship between the employment and compensation of managers and CEOs and the presence of a unionized workforce. We develop a simple efficiency wage model, with a tradeoff between higher wages for workers and more monitoring, which requires more managers. The model also assumes rent sharing between workers, managers and the owners of the firm. Unions, by redistributing rents towards the workers, lead to lower employment and lower pay for managers. Using a variety of data sets, we examine the implications of the model for the relationship between the employment and wages of managers and unionization. We find several results generally consistent with our model. (1) Both a higher fraction of unionization in an industry and region and a higher union wage differential are associated with fewer managers. (2) Managers wages are about 5 to 7 percent lower in unionized firms. (3) For CEOs the effects are larger: a 10 percent increase in unionization reduces the pay of CEOs by 2.5 percent or more.
Keywords: J51; J44; J31; 330; Executives; managers; unions; wage structure; CEOs; Führungskräfte; Arbeitsmarkt; Gehalt; Gewerkschaftlicher Organisationsgrad; USA